Factors that influence nurse manager job satisfaction: An integrated literature review. (19th October 2020) - Keith, Angela C.; Warshawsky, Nora; Neff, Donna; Loerzel, Victoria; Parchment, Joy
Abstract: Aims and objectives: To understand factors that influence nurse manager job satisfaction. Background: Nurse managers influence patient care, staff retention and health care initiatives, yet poor retention and recruiting outcomes threaten the supply of managers. Research regarding staff nurse job satisfaction and retention is substantial, but far less is known about these same areas for nurse managers. Evaluations: Electronic databases were systematically searched to find studies regarding nurse manager job satisfaction. Articles were selected using professional guidelines and set criteria. Fourteen peer‐reviewed publications were included in this review. Major themes were extracted and synthesized. Key Issues: Findings from this review indicate that nurse manager job satisfaction is influenced by workloads, organisational support, nurse manager–supervisor relationships and the quality of their training and competency. Conclusions: This review found overwhelming workloads, inadequate resources, poor supervisor relationships and insufficient training to be commonplace for nurse managers. To improve satisfaction and retention, institutions must cultivate practice environments that promote healthy workloads, strong interorganisational relationships, professional growth and success of their nurse managers. Implications for Nursing Management: Findings from this study reveal areas for improvement that health care institutions and senior nursing leadership can use to transform practice environments, increase nurse managers' job satisfaction and entice them to stay.